Monitoring Interior and Exterior Wall Inspections within a Virtual Environment - A. Z. Sampaio; D. P. Rosário; A. R. Gomes (Advances in Civil Engineering)
This paper describes two prototype applications based on the Virtual Reality (VR) technology for use in maintenance planning of buildings. In a building, the paint coating applied to interior walls and the different types of materials applied to façades convey their aesthetic character and also perform an important function of protection. This a construction component which is exposed to agents of deterioration related to its use, needing the regular evaluation of its state of repair. The applications support the performance of such periodic inspections and the monitoring of interior and exterior wall maintenance, using the VR technology. Used during an inspection visit, the applications allow users to consult a database of irregularities, normally associated with the coating, classified by the most probable causes and by the recommended repair methodologies. In addition, a chromatic scale related to the degree of deterioration of the coating, defined as a function of the time between the dates of the application of the paint and the scheduled repainting, can be attributed to each element of coating monitored. This use of the VR technology allows inspections and the evaluation of the degree of wear and tear of materials to be carried out in a highly direct and intuitive manner.